2008
DOI: 10.1667/rr1081.1
|View full text |Cite
|
Sign up to set email alerts
|

The Energetics of Rearrangement and Water Elimination Reactions in the Radiolysis of the DNA Bases in Aqueous Solution (eaqand·OH Attack): DFT Calculations

Abstract: DFT calculations on the relative stability of various nucleobase radicals induced by e(aq)(-) and (*)OH have been carried out for assessing the energetics of rearrangements and water elimination reactions, taking the solvent effect of water into account. Uracil and thymine radical anions are protonated fast at O2 and O4, whereby the O2-protonated anions are higher in energy (50 kJ mol(-1), equivalent to a 9-unit lower pK(a)). The experimentally observed pK(a)=7 is thus that of the O4-protonated species. Thermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
56
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(60 citation statements)
references
References 46 publications
4
56
0
Order By: Relevance
“…This peak cannot be definitively assigned, since we focused on dehydrogenation reactions of adenine in this work. The ring-opening reaction transients and products, as mentioned before, [40,41,[44][45][46] may present strong transitions corresponding to these shorter wavelength peaks.…”
Section: Energeticsmentioning
confidence: 54%
See 3 more Smart Citations
“…This peak cannot be definitively assigned, since we focused on dehydrogenation reactions of adenine in this work. The ring-opening reaction transients and products, as mentioned before, [40,41,[44][45][46] may present strong transitions corresponding to these shorter wavelength peaks.…”
Section: Energeticsmentioning
confidence: 54%
“…If the OH radicals add at the C 8 site, ring-opening occurs and the OD at 330 nm increases. A 2008 study by Naumov and Sonntag [46] confirmed the earlier indications that OH radicals form an adduct with adenine at the C 4 position. The adduct undergoes proton or hydrogen transfer, followed by dehydration, to form an N 6 -dehydrogenated radical.…”
mentioning
confidence: 64%
See 2 more Smart Citations
“…Reviews on these calculations can be found in Refs. [8][9][10][11][12][13]. Chemical reactivity of OH species or specific processes like hydrogen abstraction on DNA bases in gas phase have been also studied [14,15].…”
Section: Introductionmentioning
confidence: 99%